2002
DOI: 10.1021/ol0269392
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase, Pd-Catalyzed Silicon-Aryl Carbon Bond Formation. Synthesis of Sansalvamide A Peptide

Abstract: A palladium-catalyzed silicon-aryl carbon bond formation on solid-phase is reported. A phenylalanine silane resin was prepared directly from protected iodo-substituted phenylalanine with butyl diethylsilane polystyrene in one step. A rapid and high-yield solid-phase synthesis of sansalvamide A peptide was achieved from the phenylalanine silane resin. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…The identified sum formula of C 32 H 51 O 5 N 5 , from 1DF9 cosmid (RVA14), fits well with the structure of a cyclic pentapeptide. Interestingly, an identical sum formula is found in sansalvamide A peptides (22)(23)(24), synthetic derivatives of the depsipeptide natural product sansalvamide A that were isolated from a marine fungus and showed potent anti-cancer activity (25). Isolation of all identified compounds for detailed structure elucidation is currently underway.…”
Section: Resultsmentioning
confidence: 91%
“…The identified sum formula of C 32 H 51 O 5 N 5 , from 1DF9 cosmid (RVA14), fits well with the structure of a cyclic pentapeptide. Interestingly, an identical sum formula is found in sansalvamide A peptides (22)(23)(24), synthetic derivatives of the depsipeptide natural product sansalvamide A that were isolated from a marine fungus and showed potent anti-cancer activity (25). Isolation of all identified compounds for detailed structure elucidation is currently underway.…”
Section: Resultsmentioning
confidence: 91%
“…The following are examples of acidic removal of Boc groups from trimethylsilylalanines 2 [16], silylphenylalanine 4 [48,49], and silylprolines 6 and 7 [43,50]. Hydrogenolysis of Cbz groups on silicon-substituted prolines 6 has been reported [37].…”
Section: Functional Group Deprotectionmentioning
confidence: 98%
“…A number of analogs have been made. These sansalvamide A derivatives [6][7][8][9][10][14][15][16][17][18][19][20] have shown that they are privileged structures and exhibit potency against multiple targets in numerous cancer cell lines. The examples of potent cytotoxicity against pancreatic, colon, breast, prostate and melanoma cancers clearly indicate the potential of this compound class as a platform useful in targeting these cancers.…”
Section: Biological Activitymentioning
confidence: 99%
“…To evaluate their anticancer activities in vitro, we used the drug-resistant human cancer cell line HCT-116. [6][7][8][9][10] RESULTS AND DISCUSSION Structural elucidation Compound 1 was obtained as a colorless oil with the UV absorptions at l max of 232 and 275 nm. The molecular formula of 1 was established as C 40 H 51 N 5 O 5 on the basis of HRESI-MS and NMR analysis, which indicated the presence of 18 degrees of unsaturation.…”
Section: Introductionmentioning
confidence: 99%